Evaluating compliance with proper application of compression stockings in surgical patients: a clinical audit - Merin Annassery; Aravind Thayyil Raman (Clinical Medicine)
Introduction: Deep venous thrombosis (DVT) is a serious but largely preventable complication following surgical procedures, particularly in non-ambulant patients. Mechanical prophylaxis using anti-embolism compression stockings significantly reduces the risk of DVT, with studies demonstrating a 60–80% reduction in relative risk.1 However, the prophylactic effectiveness of these stockings is contingent upon correct sizing, fitting and patient adherence.2 Misapplication can lead to ineffective prophylaxis or even iatrogenic harm.3National guidelines from National Institute of Health and Care Excellence (NICE)4 and local Trust protocols5 emphasise proper use, frequent monitoring, and patient education as essential components of effective thromboprophylaxis. Materials and Methods: The objectives of the study were to evaluate the proportion of patients wearing stockings correctly, identify the most common application errors, assess staff knowledge and practices regarding sizing and fitting, and gauge patient understanding and educational needs. An audit tool was constructed to record data on parameters related to correct fitting and wearing of anti-embolism stockings. A cross-sectional audit was conducted in February and March 2025 across surgical wards. Fifty adult surgical inpatients were assessed for stocking application, focusing on correct sizing, position and observable issues, such as bunching, rolling, folded fabric or toe constriction. Patient understanding of usage instructions was also evaluated. In parallel, 25 registered nurses participated in a survey exploring their awareness of best practices, including limb measurement, fitting protocols and patient instruction. Results and Discussion: Fifty surgical patients were audited with a mean age of 59 years. 60% of patients presented with incorrectly applied stockings, with the most common problems being incorrect sizing and lack of patient education. 88% of patients did not have their limb measured before being issued compression stockings, and 69% reported not receiving any information regarding the reason for using anti-embolism stockings. Written information was not received by 100% of participants. Additionally, 25% of staff reported a lack of confidence in correct sizing and fitting. 74% of patients expressed that they would benefit from patient information leaflets and reminders from staff, while 80% of staff indicated they would appreciate a short refresher training.These findings suggest that both patient compliance and staff practice fall short of ideal standards. To improve adherence to guidelines, two main strategies are proposed: 1. Staff education: reinforce the importance of accurate limb measurement and periodic reassessment through refresher training sessions; 2. Patient education: develop and distribute clear, accessible patient information leaflets detailing the purpose, usage instructions, and care of anti-embolism stockings.5 Conclusion: Anti-embolism stockings for the prevention of DVT continue to be widely prescribed and applied with limited attention to possible contraindications, poor provision of education and information, and inadequate monitoring. Guidelines for the prescription and use of anti-embolism stockings must be strictly followed for this healthcare intervention to be effective, ensuring that both patients and staff are confident and educated in evidence-based practices for VTE prophylaxis.